PENGARUH SELF-COMPASSION TERHADAP BODY DISSATISFACTION PADA IBU ANGGOTA POSYANDU XY - Ramadhani, Sitayanti; Sholichah, Ima Fitri; Alfinuha, Setyani (Universitas Muhammadiyah Gresik, 2024)
Background: Body dissatisfaction is caused by individuals comparing theirperceived body image with other people, overestimating body shape anddrastic changes in their body. Objective: This research was conducted to testwhether there was an influence between self-compassion on bodydissatisfaction in XY integrated healthcare center mothers with a total of 46subjects. Based on the analysis results obtained from the simple linearregression test, the sig value was 0.044. Method: This research is a type ofquantitative research with simple regression analysis which measures themagnitude of the influence between the dependent variable and theindependent variable .the subjects in this study were 46 mothes were membersof posyandu XY. Result: This means that the significant value is 0.05, so it canbe seen that self-compassion (x) influences body dissatisfaction(y),Conclusion: It was concluded that the results of hypothesis testingobtained a simple linear regression value of self-compassion on bodydissatisfaction with a sig value. (2-tailed) of 0.044. Compared to thesignificance level of 0.05 (5%), this sig (2-tailed) value is 0.05 (5%) smaller.This means that there is an influence of the self-compassion variable (X) onbody dissatisfaction (Y). This research shows a figure of 0.089, which meansthe self-compassion variable contributes 8.9% to the body dissatisfactionvariable.